2020
DOI: 10.1038/s41598-020-73636-6
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A impaired cell adhesion by altering the expression of adhesion and cytoskeleton proteins on human podocytes

Abstract: Bisphenol A (BPA), a chemical -xenoestrogen- used in food containers is present in the urine of almost the entire population. Recently, several extensive population studies have proven a significant association between urinary excretion of BPA and albuminuria. The alteration of glomerular podocytes or "podocytopathy" is a common event in chronic albuminuric conditions. Since many podocytes recovered from patients' urine are viable, we hypothesized that BPA could impair podocyte adhesion capabilities. Using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 83 publications
(101 reference statements)
1
15
0
Order By: Relevance
“…* or @ means p-value < 0,05; ** or @@ means p < 0,01; *** or @@@ means p < 0,001; **** or @@@@ means p < 0,0001. Figure made with our own results published in the Journal of Cellular Physiology [22], FASEB Journal [27] and Scientific Reports [24].…”
Section: Novel Role Of Bpa In Renal Cardiovascular and Hypertensive mentioning
confidence: 96%
See 1 more Smart Citation
“…* or @ means p-value < 0,05; ** or @@ means p < 0,01; *** or @@@ means p < 0,001; **** or @@@@ means p < 0,0001. Figure made with our own results published in the Journal of Cellular Physiology [22], FASEB Journal [27] and Scientific Reports [24].…”
Section: Novel Role Of Bpa In Renal Cardiovascular and Hypertensive mentioning
confidence: 96%
“…By using transcriptomics, proteomics, western-blot, and immunocytochemistry, it was possible to determine that BPA at low doses promotes a reduction in the expression of numerous structural or adhesion proteins, such as tubulin, vimentin, podocin, cofilin-1, vinculin, E-cadherin, nephrin, and VCAM-1, as well as an increase in the expression of proteins that negatively participate in adhesion mechanisms, such as Tenascin-C [24].…”
Section: Novel Role Of Bpa In Renal Cardiovascular and Hypertensive mentioning
confidence: 99%
“…In this sense, previous studies developed by our team determined that mouse podocytes (cells that are part of the glomerular filtration barrier) treated with BPA (10 and 100 nM) underwent apoptosis followed by podocytopenia, albuminuria [12], and hypertension. Interestingly, when treating cultured human podocytes at the same doses of BPA, we observed a podocytopathy characterized by impaired cell adhesion due to alteration in the expression of the podocyte's adhesion and structural proteins [13]. Furthermore, epidemiological studies in humans have found interesting relationships between BPA concentration in blood or urine and the risk of developing kidney disease [21][22][23][24].…”
Section: Introductionmentioning
confidence: 86%
“…Currently, the European Food Safety Authority (EFSA) has delimited a tolerable daily intake (TDI) up to 4 µg/kg body weight/day, based on studies by Tyl et al (2008) on the ability of BPA to affect the kidneys [6,7]. However, only a small percentage of publications study the BPA-kidney paradigm [8][9][10][11][12][13], compared to other organs and systems such as the reproductive or endocrine systems [14][15][16][17][18][19][20]. In this sense, previous studies developed by our team determined that mouse podocytes (cells that are part of the glomerular filtration barrier) treated with BPA (10 and 100 nM) underwent apoptosis followed by podocytopenia, albuminuria [12], and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last two decades, evidence correlates BPA with other types of pathologies such as diabetes, obesity, and even cognitive and behavioral disorders [14][15][16][17]. Our group has recently found new evidence that positions BPA as a possible environmental factor promoting nephro-vascular pathologies [18][19][20][21]. Currently, few studies explore the cardiovascular system, but there are population studies that correlate high concentrations of urinary BPA with an increased risk of developing arterial hypertension [22,23].…”
Section: Introductionmentioning
confidence: 99%